Analisis Unsur Intrinsik Puisi ”Hujan Bulan Juni” dan “Tentang Matahari” Sapardi Djoko Damono - Eka Rahmawati; Syifa Salsabila (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Poetry, as a form of literary work, contains intrinsic elements that are interrelated and shape its meaning. In the poems Hujan Bulan Juni and Tentang Matahari by Sapardi Djoko Damono (1994; 1996), intrinsic elements such as physical and spiritual aspects play a significant role in conveying the message and meaning. Using the theories of Ivor Armstrong Richards (1947) and J.A. Richards (1929), this study examines elements such as line, stanza, rhyme, rhythm, figures of speech, and typography (physical elements), as well as theme, message, tone, and feeling (spiritual elements). This study aims to provide a deeper understanding of the role of these intrinsic elements in shaping the overall meaning of the poem. The research method used is descriptive analysis of the two poems. The findings suggest that these elements work together in delivering deep meaning through the structure and language used by the poet. Readers are encouraged to consider the relationship between form and meaning in understanding the message of the poems.